Perencanaan Ulang Bangunan Gedung Dormitory Kawasan Sains dan Teknologi (KST) Nuklir Yogyakarta Berbasis Building Information Modelling (BIM) 5D - Anis Salma Al Fridasari; Saka Aditama; Asri Nurdiana; Bambang Setiabudi (Jurnal Sipil dan Arsitektur, 2024)
Building Information Modeling (BIM) is a method of processing data during the life cycle of a construction project that uses three-dimensional, real-time, and dynamic building modeling software, thereby creating a complete model related to project data from the planning to the construction phase of the project. In the re-planning of the Yogyakarta Nuclear Science and Technology (KST) Dormitory Building based on Building Information Modeling (BIM) 5D, a special moment resisting frame system (SRPMK) structure was used. The planned building consists of 7 floors, including the lower structure consisting of a 50x50 square pile foundation and five types of pile cap, the upper structure consisting of columns, beams, and floor plates. The quality of concrete in the structure used is fc' 40 Mpa and 35 Mpa with reinforcing steel quality fy 420B. In this planning, 2D and 3D modeling was carried out. Structural analysis was carried out using the SAP2000 application, which was then continued with 2D 3D modeling and Quantity take-off results using Revit and Scheduling using Ms. Projects. The Draft Budget (RAB) results for this planning are Rp. 37,691,368,000.00. The planned duration of work is 26 weeks. The results of the scheduling and RAB are then integrated using the Naviswork software so that the simulation results of the work to be planned can be seen.